Facial Nerve Branching Pattern in the Parotid Region: A Cadaveric Study - Dafalla, Dr. Salah Eldeen (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: The present study’s objective was to examine the parotid region’s facial nerve branching pattern. One of the 12 pairs of cranial nerves, the facial nerve (VII), travels through the stylomastoid foramen to the parotid area. It then passes through the parotid gland’s posteromedial surface. The substance of the parotid gland has a complicated branching pattern and divides into five terminal branches. The platysma and face muscles are innervated by these branches. Based on the presence of anastomoses or communications between the terminal branches, its complicated branching pattern has been divided into many categories. Materials and Methods: Twenty-one cadaveric hemi faces were used as a sample, and the dissected specimen photos were photographed. The location of the facial nerve division, its relationship to the retromandibular vein, and the number of divisions was all documented in the dissected specimens. Results and Discussion: For head-and-neck surgeons, the facial nerve’s branching pattern is crucial. The safe removal of the parotid gland without causing facial nerve damage is key to the success of the procedure. Conclusion: The success rate of parotid procedures will be impacted by understanding of potential anatomical variances. To minimize post-operative problems, medical staff must be aware of these variations.